Relationship between Emotional Intelligence and Mathematical Problem Solving Ability - Yety Yunaeti Suryani; Supami Wihardjanti; Winarno Winarno; Muhammad Istiqlal (AlphaMath : Journal of Mathematics Education, 2023)
This study aimed to describe the level of students 'emotional intelligence, the level of students' mathematical problem-solving abilities, and the relationship between emotional intelligence and mathematical problem-solving skills. This research is a quantitative study using the ex post facto correlation method. The research sample was students of class VIII SMP Negeri 3 Teras Boyolali in the 2018/2019 academic year, and the sample was determined using the purposive sampling technique. Data were collected using questionnaires, tests, and documentation. All data were analyzed using descriptive analysis, research data using the product moment formula, and hypothesis testing. The results of the study show that: (1) The emotional intelligence of students with low emotional intelligence is 28.1%, 37.5% moderate, and 34.4% high, Mathematical problem-solving abilities of students with low math problem-solving abilities with a percentage of 29.7%, moderate 35.9%, and high 34.4%, (3) After the data were analyzed using the product moment correlation technique, the correlation coefficient value was obtained from 0.586 and then compared table r with the number. A significant level of 1%, namely 0.2075. It is proven that the results count tabel r r  in this study are substantial, in the sense of the hypothesis which states, "There is a significant relationship between emotional intelligence and the ability to solve math problems in class VIII students of SMP Negeri 3 District Teras Boyolali Regency".